Legal Protection Framework and Bankruptcy Risk Management: A Case Study of the Merah Putih Cooperative - Marpaung, Leony Ghuusbertha; Parengkuan, Deisiree Maria Rosario; Limbong, Linsepda (Fakultas Hukum Universitas Hang Tuah, 2025)
This study explores the legal protection of members of the Merah Putih Cooperative in Indonesia, focusing on the risks of losses that could lead to bankruptcy. The research problem lies in the inconsistency between the social character of cooperatives and the bankruptcy legal framework. Using a doctrinal legal analysis of Law Number 25 of 1992 on Cooperatives and Law Number 37 of 2004 on Bankruptcy and PKPU, the study identifies a gap in the legal provisions regarding the status of cooperative members in the bankruptcy process. Specifically, cooperative members, who are both owners and service users, lack clear legal standing as creditors, which exposes them to the loss of savings and economic rights. The study also finds that the principles of kinship, justice, and shared responsibility in cooperatives are not adequately integrated with the formalistic and corporatist approach of bankruptcy law. The study concludes that reformulating legal policies is necessary to accommodate the unique characteristics of cooperatives within the bankruptcy legal system. This includes recognizing the legal status of members and developing deposit protection mechanisms, ensuring a more just and responsive legal framework for the people’s economy.